Aneurysm-type plexiform lesions form in supernumerary arteries in pulmonary arterial hypertension: potential therapeutic implications - Oshima, Kaori (Am J Physiol Lung Cell Mol Physiol, 2019)
Histological observations in human pulmonary arterial hypertension (PAH) suggest a link between plexiform lesions and pulmonary supernumerary arteries. Pulmonary microvascular endothelial cells are characterized as hyperproliferative and progenitor-like. This study investigates the hypothesis that aneurysm-type plexiform lesions form in pulmonary supernumerary arteries because of their anatomical properties and endothelial characteristics similar to pulmonary microvascular endothelial cells. To induce PAH, rats were injected with Sugen5416, and exposed to hypoxia (10% O(2)) for 3 days (early stage) or 3 wk (mid-stage), or 3 wk of hypoxia with an additional 10 wk of normoxia (late-stage PAH). We examined morphology of pulmonary vasculature and vascular remodeling in lung serial sections from PAH and normal rats. Aneurysm-type plexiform lesions formed in small side branches of pulmonary arteries with morphological characteristics similar to supernumerary arteries. Over the course of PAH development, the number of Ki67-positive cells increased in small pulmonary arteries, including supernumerary arteries, whereas the number stayed consistently low in large pulmonary arteries. The increase in Ki67-positive cells was delayed in supernumerary arteries compared with small pulmonary arteries. In late-stage PAH, ~90% of small unconventional side branches that were likely to be supernumerary arteries were nearly closed. These results support our hypothesis that supernumerary arteries are the predominant site for aneurysm-type plexiform lesions in Sugen5416/hypoxia/normoxia-exposed PAH rats partly because of the combination of their unique anatomical properties and the hyperproliferative potential of endothelial cells. We propose that the delayed and extensive occlusive lesion formation in supernumerary arteries could be a preventive therapeutic target in patients with PAH.